Diaspora Identities and Psychic Trauma in V.S. Naipaul’s A House for Mr.Biswas and The Mimic Men: A Postcolonial Perspective - Ullah Bhuiyan, Mohammed Farman (International Journal of English Literature and Social Sciences (IJELS), 2019)
V.S. Naipaul is an expatriate from Trinidad whose primary business as a novelist is to project carefully and objectively the complex fate of individuals in a cross-cultural society. This proposal is about the diaspora identities and psychic trauma as represented in V. S. Naipaul’s A House for Mr. Biswas and The Mimic Men. This paper attempts to relate how these novels are replete with the theme of identity and individual psychic trauma caused by the aftermaths of colonial rule. A House for Mr. Biswas deals with the theme of isolation, frustration, and negation in a colonized society which turns cruel and callous to the aspiration of the protagonist, Mr. Mohan Biswas. Ralph Singh, on the other hand, is the narrator of The Mimic Men and he is a forty-year-old colonial minister who lives in exile in London. Singh, by writing his memoirs, tries to impose order on his life, reconstruct his identity, and get rid of the crippling sense of dislocation and displacement. This research thus attempts to analyse the different strands of identity to make the work more comprehensive and to radicalize its global demand. Though the question of identity is not new, and much work has been done on this theme of identity but still a few very important strands of identity are still untouched in Naipaul’s works. We are going to concentrate on the various types of identity and psychic trauma which are portrayed by V.S. Naipaul through different characters in different situations.